2021
DOI: 10.33188/vetheder.714491
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the presence and antibiotic resistance of listeria species and aerobic mesophilic bacteria count of cow milks

Abstract: Listeria species lead to mastitis infection in cows. The aerobic mesophilic bacteria count (total bacteria count) is one of the most important factors affecting udder health and determining the milk quality. The aim of this study was to determine the aerobic mesophilic bacteria count, one of the most important factors affecting cow's milk quality, and presence and the antibiotic resistance profiles of Listeria spp., one of the factors causing mastitis in cows. As a result of isolation and identification for Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…( 2022 ), Korsak et al. ( 2012 ) and Babacan ( 2021 ) also showed that all strains of L. innocua and L. monocytogenes from bulk tank milk and all strains of L. monocytogenes , L. innocua and L. ivanovii isolated from cow milk were susceptible to AM. On the other hand, reports of penicillin group resistance at both high and low levels have been made by some authors.…”
Section: Discussionmentioning
confidence: 89%
“…( 2022 ), Korsak et al. ( 2012 ) and Babacan ( 2021 ) also showed that all strains of L. innocua and L. monocytogenes from bulk tank milk and all strains of L. monocytogenes , L. innocua and L. ivanovii isolated from cow milk were susceptible to AM. On the other hand, reports of penicillin group resistance at both high and low levels have been made by some authors.…”
Section: Discussionmentioning
confidence: 89%